Runaway electron beam generation and mitigation during disruptions at JET-ILW. (5th August 2015) - Reux, C.; Plyusnin, V.; Alper, B.; Alves, D.; Bazylev, B.; Belonohy, E.; Boboc, A.; Brezinsek, S.; Coffey, I.; Decker, J.; Drewelow, P.; Devaux, S.; et al.
Abstract: Disruptions are a major operational concern for next generation tokamaks, including ITER. They may generate excessive heat loads on plasma facing components, large electromagnetic forces in the machine structures and several MA of multi-MeV runaway electrons. A more complete understanding of the runaway generation processes and methods to suppress them is necessary to ensure safe and reliable operation of future tokamaks. Runaway electrons were studied at JET-ILW showing that their generation dependencies (accelerating electric field, avalanche critical field, toroidal field, MHD fluctuations) are in agreement with current theories. In addition, vertical stability plays a key role in long runaway beam formation. Energies up to 20 MeV are observed. Mitigation of an incoming runaway electron beam triggered by massive argon injection was found to be feasible provided that the injection takes place early enough in the disruption process. However, suppressing an already accelerated runaway electron beam in the MA range was found to be difficult even with injections of more than 2 kPa.m 3 high-Z gases such as krypton or xenon. This may be due to the presence of a cold background plasma weakly coupled to the runaway electron beam which prevents neutrals from penetrating in the electron beam core. Following unsuccessful mitigation attempts, runaway electron impacts on beryllium plasma-facing components were observed, showing localized melting with toroidal asymmetries.